Advances in Network-Based Information Systems The 21st International Conference on Network-Based Information Systems (NBiS-2018) - Barolli, Leonard; Kryvinska, Natalia; Enokido, Tomoya; Takizawa, Makoto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the latest research findings and innovative theoretical and practical research methods and development techniques related to the emerging areas of information networking and their applications. Today's networks and information systems are evolving rapidly, and there are several new trends and applications, such as wireless sensor networks, ad hoc networks, peer-to-peer systems, vehicular networks, opportunistic networks, grid and cloud computing, pervasive and ubiquitous computing, multimedia systems, security, multi-agent systems, high-speed networks, and web-based systems. These networks have to deal with the increasing number of users, provide support for different services, guarantee the QoS, and optimize the network resources, and as such there are numerous research issues and challenges that need to be considered and addressed.
A Fuzzy-based System for Actor Node Selection in WSANs for Improving Network -- A Fuzzy-based Approach for Improving Peer Awareness and Group Synchronization in MobilePeerDroid System -- A Position Detecting System Using Supersonic Sensors for Omnidirectional Wheelchair Tennis -- Distributed Approach for Detecting Collusive Interest Flooding Attack on Named Data Networking -- An Energy-efficient Dynamic Live Migration of Multiple Virtual Machines -- Developing a Low-cost Thermal Camera for Industrial Predictive Maintenance Applications -- Effective Resource Allocation in Fog for Efficient Energy Distribution -- Efficient Energy Management using Fog Computing -- Deterrence System for Texting-While-Walking Focused on User Situation -- Slovak Broadcast News Speech Recognition and Transcription System -- Implementation of Mass Transfer Model on Parallel Computational System.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence